Hematopoietic cytokines as therapeutic players in early stages Parkinson’s disease - Farmer, Kyle; Rudyk, Christopher; Prowse, Natalie A.; Hayley, Shawn (Frontiers in Aging Neuroscience, 2015)
Parkinson's disease (PD) is a devastating age related neurodegenerative disease that is believed to have a lengthy prodromal state. It is critical to find methods of interfering with the progression of this early degenerative stage by inducing compensatory recovery processes to slow or prevent the eventual clinical symptoms. The current perspective article argues that immune system signalling molecules represent such a promising therapeutic approach. Two cytokines of interest are granulocyte macrophage-colony stimulating factor (GM-CSF) and erythropoietin (EPO). These hematopoietic cytokines have been protective in models of stroke, neuronal injury, and more recently PD. It is our belief that these trophic cytokines can be used not only for cell protection but also regeneration. However, success is likely dependent on early intervention. This paper will outline our perspective on the development of novel trophic recovery treatments for PD. In particular, we present new data from our lab suggesting that EPO and GM-CSF can foster neural re-innervation in a “mild” or partial lesion PD model that could be envisioned as reflecting the early stages of the disease.